Pendampingan dan Edukasi Penggunaan Buku Kesehatan Ibu dan Anak di Posyandu - Fitri, Lidia; Mansyur, Tri Novianty; Mildaratu, Mildaratu; Wahyuni, Tri; Ula, Zumrotul; Anto, Sardi; Wahyuni, Sri (Sahabat Sosial: Jurnal Pengabdian Masyarakat, 2024)
Maternal and child health efforts are part of the health center's mandatory health efforts. The government has implemented an integrated program through activities carried out by the Maternal and Child Health Program. The aim is to make it easy to get explanations about maternal and child health, understand the dangers that need to be taken into account during pregnancy and access services that can be obtained at health services. The PkM activity method is a pre-test activity, an exam is carried out to determine the description of the knowledge and attitudes of pregnant women regarding the use of maternal and child health books for pregnant women. This activity is carried out by asking pregnant women to fill out a questionnaire regarding the material to be presented. The results of PkM activities through mentoring and education are in an effort to increase pregnant women's knowledge about the use of Maternal and Child Health books, as well as creating innovative products to improve the health of pregnant women. Therefore, before being given education, it appears that the majority of mothers had poor knowledge, whereas after education the majority of mothers had good knowledge about the use of maternal and child health books.